Design and synthesis of hybrid cyclophanes containing thiophene and indole units via Grignard reaction, Fischer indolization and ring-closing metathesis as key steps - Kotha, Sambasivarao; Chinnam, Ajay Kumar; Shirbhate, Mukesh Eknathrao (Beilstein Journal of Organic Chemistry, 2015)
We demonstrate a new synthetic strategy to cyclophanes containing thiophene and indole moieties via Grignard addition, Fischer indolization and ring-closing metathesis as key steps.
Keywords: cyclophane; Grignard reaction; Fischer indolization; ring-closing metathesis